Digital Literacy and Parental Mediation Strategies in Managing Children’s Online Behavior in Aceh - Febri Nurrahmi; Cut Lusi Chairun Nisak; Laila Sari; Eman Alkhomees (Communicatus: Jurnal Ilmu komunikasi, 2026)
According to national data from the Indonesian Child Protection Commission (KPAI), approximately 71.3% of school-aged children in Indonesia own personal digital devices and use them for extended periods, including for non-educational purposes. In addition, 79% of children reportedly lack mutually agreed-upon rules for gadget use at home. These national trends highlight the importance of strengthening parental mediation in children’s digital activities. This issue is particularly salient in Aceh, a region with a high prevalence of misinformation, reflecting low digital literacy that affects parents’ ability to manage children’s online activities. This study aims to identify parental mediation strategies used for children aged 6–12 years, analyze factors influencing strategy selection, and explore challenges faced in digital parenting. A qualitative approach was employed, using semi-structured interviews with 15 parents of elementary school children in Banda Aceh and Aceh Besar who used digital devices. Restrictive mediation, involving rules on screen time and digital content, emerged as the most dominant strategy, followed by supervision through monitoring children’s digital activities and active mediation through discussion and explanation. Co-use, in which parents and children used digital media together, was less common. Moreover, technical mediation, involving parental control features and digital monitoring tools, was the least utilized strategy and was primarily adopted by parents with higher levels of digital literacy. The findings highlight the critical role of parental digital literacy in enhancing effective mediation strategies, contributing both theoretically to parental mediation studies and practically to digital parenting programs.